Protection of Bacillus larvae from Oxygen Toxicity with Emphasis on the Role of Catalase - Dingman, D. W. (1984)
Sporulation of Bacillus larvae NRRL B-3650 occurred only at aeration rates lower than those used for cultivation of most Bacillus species. One possible explanation for the requirement for a low level of aeration in B. larvae is that toxic forms of oxygen such as H(2)O(2) and superoxide are involved. The superoxide dismutase levels of strain B-3650 were similar to those of Bacillus subtilis 168 during sporulation, and no NADH peroxidase was present. Catalase activity was absent during exponential growth and first appeared near the start of the stationary phase. The catalase activity was 2,700 times less than that in B. subtilis 168 at the same stage of development. Therefore, the relative deficiency of catalase (and NADH peroxidase) might be the cause of the apparent O(2) toxicity. It was postulated that B. larvae might accumulate H(2)O(2) in the medium and exhibit more than normal sensitivity to H(2)O(2). Experimental results did not verify either postulate, but the possibilities of intracellular accumulation of H(2)O(2) and unusual sensitivity to endogenous H(2)O(2) were not excluded. The catalase present in early-stationary-phase cells was soluble, heat labile, and inhibited by cyanide, azide, and hydroxylamine. An increase in catalase activity also occurred at the time of appearance of refractile spores in both B. larvae NRRL B-3650 and B. subtilis 168. The level of catalase activity in strain B-3650 was 5,400 times less than that in B. subtilis 168 at this stage. In B. larvae, this second increase occurred primarily within the developing endospore. The activity in spore extracts was particulate, heat stable, and inhibited by hydroxylamine but not by azide or cyanide. Synthesis of catalase in B. larvae was unaffected by H(2)O(2), O(2), or glucose.